Current and Future Treatments for Graves’ Disease and Graves’ Ophthalmopathy - Kotwal, Anupam; Stan, Marius (Hormone and Metabolic Research, 2018)
The course and pathogenesis of Graves’ disease and Graves’ ophthalmopathy are interdependent, influencing each other’s therapeutic choices. Multiple factors including geographic location, access to medical services, patient and physician preferences influence the management of these conditions. Graves’ disease is classically managed with one of three treatment options – antithyroid drugs, radioactive iodine, and thyroidectomy. In recent years, there has been a shift towards antithyroid drugs, including long term therapy with these agents, given the advantage of avoiding hypothyroidism and the apparent safety of this approach. In addition, new therapies are (slowly) emerging, focusing on immunomodulation. Technological advances are opening doors to non-pharmaceutical interventions that aim to deal with both structural thyroid abnormalities as well as biochemical abnormalities of hyperthyroidism. Graves’ ophthalmopathy management is guided by its activity and severity status, with treatment options including smoking cessation, control of hyperthyroidism, local eye measures, glucocorticoids, selenium, orbital radiotherapy, and surgery. In addition to these established treatment choices, new immunotherapy-based approaches are being tested. Some of them (tocilizumab and teprotumumab) are very promising but further evaluation is needed before we can establish their role in clinical care. Agents identified as beneficial in Graves’ disease management will likely be tested in Graves’ ophthalmopathy as well. In the coming years, our main clinical responsibility will be to find the proper balance between the benefits and potential risks of these incoming therapies, and to identify the subgroups of patients where this ratio is most likely to favor a safe and successful therapeutic outcome.
Keywords: autoimmunity; thyroid function; hyperthyroidism; immunotherapy